1996
DOI: 10.1149/1.1837172
|View full text |Cite
|
Sign up to set email alerts
|

Electrochromic Behavior of Molybdenum Trioxide Thin Films, Prepared by Thermal Oxidation of Electrodeposited Molybdenum Trisulfide, in Mixtures of Nonaqueous and Aqueous Electrolytes

Abstract: Electrochromic molybdenum trioxide thin films were prepared by thermal oxidation in air of electrodeposited molybdenum trisulfide. MoO, prepared at temperatures ranging from 400 to 550°C were found to be polycrystalline. The best electrochromic properties (coloration efficiency and coloration time) evaluated in 1 M LiClO4/propylene carbonate were observed for films prepared by annealing at 425°C for 10 mm. The coloration efficiency (35 cm'/C) for these optimum films compare well with those reported in the lite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
1

Year Published

1997
1997
2016
2016

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(8 citation statements)
references
References 11 publications
1
5
0
1
Order By: Relevance
“…In a real-time device, the electrochromic metal oxide is coated as a thin film over a suitable (often transparent) substrate. The deposition method strongly affects the adhesion, occurrence, and variations of the photo/electro-optic effect in the films. , It also alters the morphology, leading to a change in impedance, the diffusion of intercalating species, and electrode reaction kinetics. Different film growth techniques are currently used for molybdenum oxide thin film deposition such as electron beam evaporation , sputtering, chemical vapor deposition (CVD), and electrodeposition. …”
Section: Introductionmentioning
confidence: 99%
“…In a real-time device, the electrochromic metal oxide is coated as a thin film over a suitable (often transparent) substrate. The deposition method strongly affects the adhesion, occurrence, and variations of the photo/electro-optic effect in the films. , It also alters the morphology, leading to a change in impedance, the diffusion of intercalating species, and electrode reaction kinetics. Different film growth techniques are currently used for molybdenum oxide thin film deposition such as electron beam evaporation , sputtering, chemical vapor deposition (CVD), and electrodeposition. …”
Section: Introductionmentioning
confidence: 99%
“…However, we have observed that postdeposition heat treatment of these films at relatively low temperatures (e450 °C) markedly influences the overall electroinsertion properties (insertion kinetics and charge storage capacity). While others [23][24][25] have briefly discussed the influence of sintering temperature on structural features and electroinsertion properties of electrodeposited MoO 3 thin films, to our knowledge no detailed investigations concerning the effect of film microstructure, metal oxidation state, and water content on the electrochromic and ion storage behavior have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…where Q in (mC cm 22 ) is the charge injected during the colouration cycle. The Q in was calculated by integrating the current density of the colouration cycle between the starting and ending time of each period according to the following equation…”
Section: Od~logmentioning
confidence: 99%